Quality of Education Services and Community Satisfaction with SDIT Using The Servqual Model - Syska Lady Sulistyowatie; Arif Julianto Sri Nugroho; Abdul Haris; Agung Nugroho Jati; Tasari (Widya Accarya, 2024)
This research develops a model through measuring the quality of educational services towards the competitive excellence of SDIT (Integrated Islamic Primary Schools). This research aims to test the gap scores for each dimension of each SDIT, thus it can determine the right marketing strategy to satisfy and increase the interest of new students’ parents who believe that their children will receive an education at an excellent Islamic Elementary School. The research was using a quantitative approach through respondent description, item validity and reliability, and ServQual model statistical tests. The population in the research was all people who believe in Integrated Islamic Primary School education in Klaten Regency. This research used a purposive sampling technique of 100 respondents. The attributes in the questionnaire were adapted from the ServQual concept which is suitable in the realm of educational research including tangibles, reliability, responsiveness, assurance and empathy. Quantitative tests include validity tests, item reliability and ServQual confirmation tests. The test results of validity and reliability were valid and reliable. The confirmation test score has a positive average value of 60.27 with the lowest positive value in the reliabilities dimension of 28.45, followed by tangibles 34.28, responsiveness 72.58 assurance 88.44 and empathy has the highest value of 127.60. Improvement efforts must continue to be made by the SDIT management with an emphasis on improving the value that still has the lowest positive dimension followed by the next positive value. Increasing the quality of SDIT's educational services by implementing the Total Quality Management concept optimally will lead to increased community satisfaction and strengthened SDIT's competitive performance in the future.